2020
DOI: 10.3390/su12114361
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Measurement of Green Regional Development and Its Influencing Factors: An Improved Data Envelopment Analysis Framework

Abstract: Reasonably assessing the efficiency of green regional development is a key to improving environmental management and implementing sustainable development strategies. From the perspectives of environmental pollutant emissions, energy consumption, and production factor cost, the non-radial data envelopment analysis model based on the Malmquist index was applied to measure the green development efficiency and regional differences of 11 cities in Zhejiang from 2007 to 2016 from both static and dynamic aspects. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…Moreover, foreign direct investment has a significant positive impact on green total factor productivity, while government intervention has a significant negative impact. The regression coefficient of government intervention is negative, meaning that the government intervention is unreasonable and causes the loss of green total factor productivity in the YREB, which is in line with the conclusion of Lu et al [35] The regression coefficient of FDI is positive, which suggests that foreign direct investment can promote green technology spillover and technology innovation in the YREB, thereby helping to improve regional green total factor productivity, which also confirms the study of Ayamba et al [31]. Based on the above conclusions, hypothesis 2 is confirmed.…”
Section: Impact Of Environmental Regulations On Gtfpsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, foreign direct investment has a significant positive impact on green total factor productivity, while government intervention has a significant negative impact. The regression coefficient of government intervention is negative, meaning that the government intervention is unreasonable and causes the loss of green total factor productivity in the YREB, which is in line with the conclusion of Lu et al [35] The regression coefficient of FDI is positive, which suggests that foreign direct investment can promote green technology spillover and technology innovation in the YREB, thereby helping to improve regional green total factor productivity, which also confirms the study of Ayamba et al [31]. Based on the above conclusions, hypothesis 2 is confirmed.…”
Section: Impact Of Environmental Regulations On Gtfpsupporting
confidence: 87%
“…Foreign direct investment (FDI): It is generally believed that FDI affects green total factor productivity through capital formation, technology transfer, technology spillover, and environmental spillover, but the results are often regionally heterogeneous and related to the intensity of environmental regulation. This paper adopts the ratio of actual utilized FDI to GDP as an FDI variable [35,36].…”
Section: Control Variablesmentioning
confidence: 99%
“…However, human capital and degree of openness show a negative impact [ 28 ]. Some studies stated that there is no significant relationship between environmental regulation and industrial ecological efficiency [ 29 ], but others showed that the interaction between government intervention and environmental regulation has a significant impact on green development [ 30 ]. Although the industrial structure has a negative impact, there is no denying the positive promotion effect of the rationalization of industrial structure and upgrading of industrial structure [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In academia, GD has been studied from both theoretical and practical perspectives, including the conceptualization connotation of GD (Colglazier, 2015; Csete & Horvath, 2012; Grillitsch & Hansen, 2019), its influence factors (Feng et al., 2017; Lu et al., 2020), and evaluations of development level and efficiency (Brito et al., 2019; Wu et al., 2020; Zhang et al., 2020). Scholars have attempted to construct an evaluation index system for GD by studying GD's conceptualization and influencing factors.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%